ANALISIS DETERMINAN BRAND LOYALTY SINGKONG KEJU D9 - Bernardus Ardika Stefano; Yuliawati (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2019)
The purpose of this research is describe the general description of the characteristics of respondents singkong keju D9 and to find out the relationship between product quality, price perception, promotion, brand image and brand trust with brand loyalty in singkong keju D9. This research method is quantitative descriptive. The data used are secondary data and primary data. The method of data collection is done by distributing questionnaires to consumers of singkong keju D9. Respondents were selected using the accidental sampling method. The data analysis technique used to answer the hypothesis of this study is validity test, reliability test, and rank spearman correlation test. The results of this study indicate that in the general description the characteristics of respondents found in the gender are dominated by men; with age that falls into the final adult category; employment is dominated by students, entrepreneurs, and civil servants; monthly income is categorized as medium; the number of purchases in one month into the category rarely; the purpose of the purchase is for personal consumption and souvenirs and product quality, price perception, promotion, brand image, and brand trust have a moderate and positive relationship to brand loyalty.